FINANCIAL ANALYSIS OF SMOKED PATIN FISH (Pangasius sp) IN UMKM SALAI DUA PUTRI, KOTO MASJID VILLAGE, KAMPAR REGENCY, RIAU PROVINCE - Pamaharyani, Luchiandini Ika; Putri, Hersa Kumala (Politeknik Kelautan dan Perikanan Dumai, 2025)
Catfish (Pangasius sp.)